Transfusion-transmitted malaria: donor prevalence of parasitaemia and a survey of healthcare workers knowledge and practices in a district hospital in Ghana - Owusu-Ofori, Alex (Malar J, 2016)
BACKGROUND: Transfusion-transmitted malaria (TTM) is a risk of transfusion that has not been well described in malaria endemic regions. The risk of the recipient getting malaria is related to the prevalence of malaria in the blood donors. There is however little information on the prevalence of malaria among donors in Akatsi district of Ghana. Further, the knowledge and practices of healthcare workers to TTM is unknown. The study was undertaken to determine the prevalence of malaria parasite infection among blood donors and to evaluate the knowledge and practices of healthcare workers to TTM in the Akatsi district of Ghana. METHODS: The study was conducted at Akatsi South District Hospital between May and August 2014. To screen for Plasmodium falciparum, 5 µl of capillary blood was obtained by finger prick from 200 participants (100 donors and 100 healthy controls). Plasmodium falciparum screening was done using CareStart™ Malaria Antigen kit. To obtain information regarding TTM knowledge and practices, questionnaires were completed by 100 health workers including nurses, doctors and laboratory staff. RESULTS: The prevalence of P. falciparum was the same (10 %) in both donors and controls. All those who were malaria RDT positive were aged 15–25 years. Out of the 100 healthcare workers (31 males and 69 females) surveyed, 45 % of respondents (45/100) had never heard of transfusion-transmitted malaria. Almost all respondents (91 %) had not attended any lecture/seminar/workshop on blood transfusion in the past 12 months. There were 44 respondents (44 %) who wrongly said malaria was being screened for prior to transfusion in their hospital. However, 98.2 % (54/55) of those who had heard about TTM rightly stated that TTM can be prevented. CONCLUSION: The prevalence of P. falciparum parasitaemia is 10 % in healthy blood donors in the Akatsi district and represents a risk for TTM though the extent of this risk is unclear. Knowledge about TTM in healthcare workers in the district is low. Continuous education and in-service training may be a means to improve TTM knowledge and preventive practices by the health workers in the district.